2022
DOI: 10.1159/000526819
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Experiences of Undergraduate Nursing Students on Clinical Learning Environment in a Public University

Abstract: <b><i>Background:</i></b> Clinical learning is viewed as a fundamental and essential part of nursing education. Clinical training offers chances to use the theoretical knowledge in practice, raise problem-solving and executive skills, learn time management, collaborate with others, and develop professionalism. <b><i>Objective:</i></b> This study intended to reveal the perceptions and experiences of the clinical learning environment of undergraduate nursing studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Students generally had a positive perception of their clinical instructors, and this is consistent with the study of Jacobsen et al (2019) in Norway. They viewed instructors as role models, especially when instructors displayed professionalism, systematic approaches to their work, familiarity with clinical settings, and effective management of student clinical practice ( Niederriter et al, 2017 ; Rozario et al, 2022 ). Students indicated that their clinical instructors effectively communicated expectations for clinical practice ( Bazrafkan & Kalyani, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Students generally had a positive perception of their clinical instructors, and this is consistent with the study of Jacobsen et al (2019) in Norway. They viewed instructors as role models, especially when instructors displayed professionalism, systematic approaches to their work, familiarity with clinical settings, and effective management of student clinical practice ( Niederriter et al, 2017 ; Rozario et al, 2022 ). Students indicated that their clinical instructors effectively communicated expectations for clinical practice ( Bazrafkan & Kalyani, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the important factors that could influence the learning experiences of nursing students is the CLE. A positive CLE is characterized by well-oriented students, supportive staff ( Mbakaya et al, 2020 ), cooperative preceptors ( Ford et al, 2016 ), approachable and experienced clinical instructors ( Jacobsen et al, 2019 ; Niederriter et al, 2017 ; Oermann et al, 2022 ), availability of resources, and the integration of theory and practice ( Rozario et al, 2022 ). Such an environment could enhance the overall student's learning experiences ( Ford et al, 2016 ), self-confidence, and motivation to learn ( Jonsén et al, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Inadequate resources and facilities were another extracted category. Evidence suggests this problem negatively affects nursing education in different societies (9,22,35). The lack of equipment is considered the cause of nurses' disappointment in decision-making, delayed care, and emotional tensions.…”
Section: Discussionmentioning
confidence: 99%